2015
DOI: 10.1080/07908318.2015.1032303
|View full text |Cite
|
Sign up to set email alerts
|

Tasks and learner motivation in learning Chinese as a foreign language

Abstract: This study focuses on how beginner learners in a task-based teaching and learning (TBTL) environment perceive what is motivating to them in the process of learning Chinese as a foreign language at Aalborg University, Denmark. Drawing upon empirical data from surveys, group interviews and participant observation, this study explores which kinds of tasks are perceived as motivating from the students' perspective and which characteristics the learners associate with motivating tasks. The study indicates that it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Cai and Zhu [9] employed the LMSS as a framework to explore the impact of an online learning project on university students' CAL learning motivation in the United States, and reported that L2 learning experiences changed significantly before and after the online project. Ruan et al [5] examined the influence of task-based instruction on beginner CAL learners' motivation in a Danish university. The result demonstrated that unfocused tasks and tasks involving group work, interactions, learner autonomy, and cultural elements could motivate the learners.…”
Section: Motivation For Learning Chinese As An Additional Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Cai and Zhu [9] employed the LMSS as a framework to explore the impact of an online learning project on university students' CAL learning motivation in the United States, and reported that L2 learning experiences changed significantly before and after the online project. Ruan et al [5] examined the influence of task-based instruction on beginner CAL learners' motivation in a Danish university. The result demonstrated that unfocused tasks and tasks involving group work, interactions, learner autonomy, and cultural elements could motivate the learners.…”
Section: Motivation For Learning Chinese As An Additional Languagementioning
confidence: 99%
“…By the end of 2018, more than 2.7 million people from 154 countries/regions were reportedly learning Chinese as an additional language (CAL) through various learning modes [4]. Despite the rising number of CAL learners both in and outside China, CAL teachers have reported a number of challenges that are related to this study, such as difficulties in generating and sustaining learning motivation [5], low learner retention rates [6][7][8], and a lack of research on Chinese language learning motivation [9,10]. For this reason, there is a pressing need for researchers to explore CAL learners' motivation in diverse teaching and learning contexts [5].…”
Section: Introductionmentioning
confidence: 99%
“…He found out that integrative motivation represents a major positive role and language anxiety represents a major negative role in both sociocultural adaptation and academic adaptation. Researchers at Aalborg University (Ruan, Duan, & Du, 2015) discovered that integrative motivation played a more significant role than instrumental motivation in the learning process.…”
Section: Motivation and Slamentioning
confidence: 99%
“…Moreover, learner's attitudes and motivation are both important for second language acquisition (Dörnyei, 2001). Ruan, Duan, and Du (2015) suggest that Chinese is often regarded as a difficult language to learn in Western countries and argue that it is therefore necessary to increase the motivation of learners-especially for beginners with low language skills-when conducting a task-based class. Rueda and Chen (2005) purport that cultural differences can influence the assessment of motivational processes in second and foreign language learning.…”
Section: Cross-cultural Learning and Second Language Learningmentioning
confidence: 99%